Impact of the Topical Ophthalmic Corticosteroid Loteprednol Etabonate on Intraocular Pressure - Sheppard, John D. (Adv Ther, 2016)
Corticosteroids are a mainstay therapeutic option for the treatment of ocular inflammation. However, safety remains a concern for clinicians, particularly with long-term use. Though highly effective at suppressing inflammatory and allergic responses, topical ophthalmic corticosteroids carry an inherent risk of side effects, including elevated intraocular pressure (IOP), a risk factor for the development of glaucoma. The corticosteroid loteprednol etabonate (LE) contains an ester rather than a ketone at the C-20 position, minimizing the potential for side effects, including IOP elevation. In early pivotal clinical trials of LE ophthalmic suspension for conjunctivitis (allergic, giant papillary), anterior uveitis, and post-operative inflammation, LE had minimal impact on IOP over short-term (<28 days) and long-term (≥28 days) use. Since then, new LE formulations—including a gel, an ointment, and a suspension of LE in combination with tobramycin—have become commercially available. Multiple studies evaluating the safety and efficacy of LE for inflammatory conditions have been reported, including those requiring longer-term treatment such as photorefractive keratectomy, corneal transplantation, and dry eye disease. We review the available published data on the effect of LE on IOP and report on the cumulative incidence of clinically significant IOP elevations (≥10 mm Hg from baseline) with short-term and long-term LE use. In all studies, LE consistently demonstrated a low propensity to elevate IOP, regardless of formulation, dosage regimen, or treatment duration, including in known steroid responders. The cumulative proportion of patients exhibiting clinically significant IOP increases was 0.8% (14/1725 subjects) in studies evaluating short-term LE treatment and 1.5% (21/1386 subjects) in long-term studies. Furthermore, use of LE was associated with significantly lower rates of IOP elevation ≥10 mm Hg as compared to prednisolone acetate or dexamethasone (when used in combination with tobramycin). The cumulative data to date substantiates a favorable IOP-safety profile for LE with both short-term and long-term use.